HOW A HEALTHY LIFESTYLE CAN PREVENT OR SLOW THE ONSET OF PARKINSON’S DISEASE - Tanvi Koppula (International Educational Journal of Science and Engineering, 2025)
Parkinson’s disease (PD) is the second most common neurodegenerative disease, right after Alzheimer’s disease (AD). This paper aims to give a holistic overview of the factors (including diet, exercise, sleep, and mental wellness) that can directly impact brain health and the chances of developing PD. Regular exercise has varied effects on neurological health, including increased neuroplasticity, reduced neuroinflammation, and increased dopamine levels. 30 minutes of exercise per day is optimal to promote heart, brain, and overall body health. The diet also plays an important role in promoting brain health. This paper draws attention to the Mediterranean diet, which comprises several foods composed of naturally occurring anti-inflammatory agents and antioxidants, e.g., polyphenols. Omega-3 fatty acids are instrumental in maintaining brain structure. Sleep is vital for maintaining neurological health. The glymphatic system removes the potentially neurotoxic waste built up in cells. This reduces the risk of neuroinflammation. Better sleep also promotes better mental well-being, and blue light exposure before sleeping should be avoided for restful sleep. Disruptions to the circadian rhythm could mean a higher risk for Parkinson’s disease. Prioritizing mental well-being is important to reduce the risk of chronic stress and neuroinflammation. Early life stress can greatly augment a person’s chances of getting Parkinson’s disease. Stress management, of any form (e.g., meditation, praying, having companion animals), can help alleviate stress.